Vacuolization of mucolipidosis type II mouse exocrine gland cells represents accumulation of autolysosomes - Boonen, Marielle (The American Society for Cell Biology, 2011)
We previously reported that mice deficient in UDP-GlcNAc:lysosomal enzyme GlcNAc-1-phosphotransferase (mucolipidosis type II or Gnptab −/− mice), the enzyme that initiates the addition of the mannose 6-phosphate lysosomal sorting signal on acid hydrolases, exhibited extensive vacuolization of their exocrine gland cells, while the liver, brain, and muscle appeared grossly unaffected. Similar pathological findings were observed in several exocrine glands of patients with mucolipidosis II. To understand the basis for this cell type–specific abnormality, we analyzed these tissues in Gnptab −/− mice using a combined immunoelectron microscopy and biochemical approach. We demonstrate that the vacuoles in the exocrine glands are enlarged autolysosomes containing undigested cytoplasmic material that accumulate secondary to deficient lysosomal function. Surprisingly, the acid hydrolase levels in these tissues ranged from normal to modestly decreased, in contrast to skin fibroblasts, which accumulate enlarged lysosomes and/or autolysosomes also but exhibit very low levels of acid hydrolases. We propose that the lysosomal defect in the exocrine cells is caused by the combination of increased secretion of the acid hydrolases via the constitutive pathway along with their entrapment in secretory granules. Taken together, our results provide new insights into the mechanisms of the tissue-specific abnormalities seen in mucolipidosis type II.